Optimization for maximum extraction of solder from waste PCBs through grey relational analysis and Taguchi technique. (1st January 2022) - Soni, Anisha; Patel, Rigal Manubhai; Kumar, Kartik; Pareek, Kapil
Highlights: Leaching solution optimization is done by Taguchi and GRA. L27 experimentations for 4 control factors and 3 levels were performed. Optimal solution found at 2.5, 0.40 mol/l (HBF4, H2 O2 ), 3.0 % HNO3 and 40 min. Contribution of HNO3, HBF4, H2 O2 and time are 25.69 %, 0.99%, 14.65% and 0.23%. Abstract: Recycling of waste printed circuit boards (WPCBs) is desirable to protect the environment and recover the valuable materials. In this regard, dissolution of solder is a key step to recycle the WPCBs. In this work, optimization for maximum dissolution of solder with minimum dissolution of copper is carried out by using Taguchi optimization method. Grey Relational Analysis (GRA) is used for converting multi-response into single response on the basis of Grey Relational Grade (GRG) value. The optimal solution is then achieved by applying Taguchi method on the GRG values achieved from GRA. The results show optimal control factors value of 2.5 mol/l (HBF4 ), 0.40 mol/l (H2 O2 ), 3.0 % HNO3 and 40 min with maximum Signal/Noise ratio (S/N) −8.31. The treated WPCB with above chemical concentration and time exhibits the complete dissolution of solder and removal of the components without any undesired effect of fading of colour, symbol and characters on the printed circuit board (PCB) surface.